Organic farming and biodiversity - Elisabeta Roșu (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 14th Edition, 2023)
Organic farming is a sector with real development potential in Romania, being an essential instrument on the way to environmental protection, through the conservation of soil, improvement of water quality and support to biodiversity. The present paper aims to analyses the evolution of organic farming, both at national and county level. Year by year, the areas under organic farming and the number of organic operators, mostly farmers, have increased. The counties Tulcea and Timi÷s have the largest areas under organic farming, and most operators in organic farming work in the counties Sæalaj and Satu Mare. The organic farming provides a favorable framework for maintaining biodiversity, using friendly, economically and socially efficient practices for farms, generating modern attributes for rural communities, and offering a different lifestyle and a different quality of life for the entire society.
Keywords: Q15; R1; 330; organic farming; nature protection; biodiversity